Effects of supplemental ground grain sorghum during grazing of endophyte-infected tall fescue on grazing and subsequent feedlot performance of steers - A.S. Freeman; K.P. Coffey (Kansas Agricultural Experiment Station Research Reports, 1991)
Sixty-three crossbred steers (740 lb BW) were used to evaluate the effects of energy supplementation during grazing of endoplyte-infected tall fescue and on their subsequent feedlot performance. Grazing ADG was .53 lb/d for control (no supplementation) vs. .81 and 1.21 lb/d with .25% and .5% of BW as ground sorghum (GS), respectively. Grazing supplementation did not affect (P>.10) feedlot performance. Steers receiving .25% GS were 2.3% and 6.2% more efficient (P<.07) during the feedlot phase than 0% and .5% GS steers, respectively. The .5% GS steers were 3.8% less efficient (P<.07) during the feedlot phase than the 0% GS steers. Steers receiving grazing supplementation had increased (P<.07) adjusted backfat measurements and less desirable (P<.02) yield grades than non-supplemental controls. Supplementing steers grazing endophyte-infected fescue at .25% of BW with ground grain sorghum improved feedlot feed conversion compared to no supplementation and supplementing at .5% BW.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Sorghum grain; Steers; Grazing performance; Feedlot Performance; Fescue; Endophyte